Experimental study on sand production of depleted oil and gas reservoirs - Zhang, Yuda; Yuan, Guangjie; Dong, Jingnan; Liu, Tianen; Qiu, Yiwang; Wu, Qiubo; Zang, Chunyang; Ding, Jiajie (Frontiers in Earth Science, 2023)
With the increasing demand for natural gas, the emergency peak shaving capacity of gas storage is facing great challenges. The operation of gas storage converted from depleted oil and gas reservoir has the characteristics of strong injection and production, and alternate injection and production. However, the sand production of the reservoir makes the major gas storages face the dilemma that the injection and production capacity cannot be enhanced. In this study, the impact factors of sand production in injection-production wells of gas storage converted from depleted oil and gas reservoir were analyzed, and the sand production simulation device of gas storage was developed. Aiming at the two main controlling factors of alternating load and flow, the experimental study of quantitative sand production was conducted. The experimental results show that the alternating load has a significant weakening effect on the reservoir, and the sand production is positively correlated with the number, size and span of the alternating load exerted on the reservoir. By the method of multiple regression analysis, the parameters affecting the sand production degree of the core were obtained as follows: the upper and lower limit pressure of the alternating load, the flow rate and the number of alternating loads. The sand production map was obtained by combining the sand production amount of the core and the upper limit pressure of the alternating load to evaluate the sand production degree of the injection-production wells. In addition, at the same flow rate, the ratio of sand yield of two alternating loads stages is approximately equal to the constant, which provides a reference for the prediction of sand production in gas storage. The indoor simulation experiment of sand production in gas storage provides technical ideas and theoretical basis for the reconstruction of gas storage in Nanpu 1–29 block, and guides the selection of sand control completion methods in gas storage.